2009
DOI: 10.1007/s12230-009-9102-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora erythroseptica (Pink Rot) Development in Russet Norkotah Potato Grown in Buffered Hydroponic Solutions II. pH Effects

Abstract: Pink rot caused by the pathogen Phytophthora erythroseptica Pethyb. causes severe pre-and post-harvest losses in potato. Severe losses of potato from pink rot infection suggest the need for better information on cultural factors associated with disease development. Soil pH has been regarded as a strong influence on disease development as observed by previous studies and by commercial potato growers. A hydroponic growth system was established to study the effects of pH on P. erythroseptica infection and coloniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Commonly used hydroponic solutions, such as Hoagland and Arnon (1950) and Steinberg (1953), are readily modified to study chemistry impacts, such as pH, (Bensen et al 2009a) and to create individual nutrient deficiencies, such as N (Geary et al 2015), P (Summerhays et al 2017), K (Hughes, Jolley, and Brown 1992), Ca (Bensen et al 2009b), Fe (Brown et al 1990;Buxton et al 2012;Hopkins, Jolley, and Brown 1992a, 1992b, 1992c, Zn (Hopkins et al 1998), and Mo (Steinberg 1953). Nutrient interaction studies have also been accomplished, such as P and Zn (Barben et al 2010a(Barben et al , 2010cNichols et al 2012), P and Mn (Barben et al 2010b), andP, Zn, andMn (Barben et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used hydroponic solutions, such as Hoagland and Arnon (1950) and Steinberg (1953), are readily modified to study chemistry impacts, such as pH, (Bensen et al 2009a) and to create individual nutrient deficiencies, such as N (Geary et al 2015), P (Summerhays et al 2017), K (Hughes, Jolley, and Brown 1992), Ca (Bensen et al 2009b), Fe (Brown et al 1990;Buxton et al 2012;Hopkins, Jolley, and Brown 1992a, 1992b, 1992c, Zn (Hopkins et al 1998), and Mo (Steinberg 1953). Nutrient interaction studies have also been accomplished, such as P and Zn (Barben et al 2010a(Barben et al , 2010cNichols et al 2012), P and Mn (Barben et al 2010b), andP, Zn, andMn (Barben et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Goodwin et al (1997) reported that the level of calcium in canola leaf extracts was significantly correlated to disease resistance and to inhibition of PG activity by Leptosphaeria maculans. Increasing calcium content of beans decreased the activity of PG and pectate transeliminase thereby increasing resistance to Pcc (Krauss, 1999) while Benson et al (2009) showed that pink soft rot disease infection and severity decreased with an increase in the available calcium between 3 and 343 mg/L.…”
Section: Mechanisms Of Calcium Induced Resistance To Soft Rotmentioning
confidence: 99%
“…Many hydroponic solutions are available, such as Hoagland and Arnon [10] and Steinberg [11]. In many cases, the original published solutions have been modified to study chemistry impacts such as pH [12], and various hydroponic solutions have been used to create individual nutrient deficiencies, such as nitrogen (N) [13,14], phosphorus (P) [8,[15][16][17][18][19][20], potassium (K) [21], sulfur (S) [22], calcium (Ca) [23,24], magnesium (Mg) [25], iron (Fe) [21,[26][27][28][29], zinc (Zn) [15,[17][18][19]30], manganese (Mn) [16,18,31], copper (Cu) [32], boron (B) [33], molybdenum (Mo) [11], chloride (Cl) [34], and nickel (Ni) [35].…”
Section: Introductionmentioning
confidence: 99%